Crystallographically engineered hierarchical polydomain nanostructures in perovskite ferroelectric films. (1st June 2019) - Tan, Congbing; Ouyang, Jun; Zhong, Xiangli; Wang, Jinbin; Liao, Min; Gong, Lunjun; Ren, Chuanlai; Zhong, Gaokuo; Zheng, Shuaizhi; Guo, Hongxia; Zhou, Yichun
Abstract: Hierarchical polydomain nanostructures, usually formed in epitaxial films, serve to fully relax the misfits between the film and substrate, as well as the strains between the poly-twin variants of the film material. The minimization of the elastic energy endows this type of structure superior stability over other domain architectures. However, the existence of energetically degenerate polytwin variants and their intersecting domain boundaries often led to undesirable functional properties in non-engineered films. Here we show that such nanostructures in epitaxial perovskite ferroelectric films can be crystallographically engineered to eliminate intersecting domain boundaries, thereby achieving an improved ferroelectric performance. In addition to a reduced coercive field and increased dielectric and piezoelectric responses, this type of ferroelectric polydomain nanostructure shows an enhanced ferroelectric polarization with a substantially improved fatigue resistance, as opposed to non-engineered nanostructures with intersecting domain boundaries. These findings suggest an alternative route for the fabrication of highly-reliable nonvolatile ferroelectric memory devices, and may find broader applications in piezoelectrics and energy storage. Graphical abstract: Image 1